Design and Implementation of Social Safety Nets in Tanzania: A Systematic Review - Msuha, Basil; Kissoly, Luitfred D.; Kihaule, Arnold (International Journal of Economics and Financial Issues, 2024)
Social safety nets (SSNs) in Africa have become a key strategy for addressing poverty and vulnerability. However, the effectiveness of this policy instrument is dependent on design and implementation features. Much of the evidence on the design and implementation of SSNs from systematic literature reviews is skewed toward Latin America, Asia, and to a limited extent, Africa. Using preferred reporting items for systematic reviews and meta-analyses (PRISMA) methodology we aim to address this gap. Based on evidence extracted from 17 studies, we found more than 12 SSNs types in Tanzania, grouped into cash-based transfers, in-kind-based transfers, and public works which is consistent with the view that every country in Sub-Saharan Africa is implementing at least one type of SSNs. Subsequently, we found that the SSNs do not have a recertification program because most them were designed as time-bound, for which recertification was not necessary; and they were initially conceived to alleviate chronic poverty; thus, a maximum duration was not needed. Yet, existing design and implementation features generate inefficiency through duplications and overlaps, and limit potential coverage and performance.